2021
DOI: 10.3390/jcm10061261
|View full text |Cite
|
Sign up to set email alerts
|

Management Challenges in Chronic Obstructive Pulmonary Disease in the COVID-19 Pandemic: Telehealth and Virtual Reality

Abstract: For the treatment of chronic obstructive pulmonary disease (COPD), early diagnosis and unconditionally correct management at the initial stage of the disease are very important when the symptoms are not yet too worrying. In this way, the progress of the disease can be slowed down, as can the occurrence of late, life-threatening symptoms. Pulmonary rehabilitation is an essential component of the management of COPD. The selection of appropriate exercises, which are determined during the classification of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 63 publications
1
62
0
4
Order By: Relevance
“…In the era of required social distancing because of the COVID-19 pandemic, almost all of the center-based pulmonary rehabilitation programs temporarily shut down, and at the time of this paper they have still only re-opened to a limited degree. This has led to the use of telemedicine technology to provide elements of pulmonary rehabilitation to those who need it, yet who—because of their age, disease severity, and frequent co-morbid conditions—would be at risk in the crowded settings of traditional pulmonary rehabilitation [ 63 ]. How this will play out once the pandemic subsides remains to be determined.…”
Section: Telemedicinementioning
confidence: 99%
“…In the era of required social distancing because of the COVID-19 pandemic, almost all of the center-based pulmonary rehabilitation programs temporarily shut down, and at the time of this paper they have still only re-opened to a limited degree. This has led to the use of telemedicine technology to provide elements of pulmonary rehabilitation to those who need it, yet who—because of their age, disease severity, and frequent co-morbid conditions—would be at risk in the crowded settings of traditional pulmonary rehabilitation [ 63 ]. How this will play out once the pandemic subsides remains to be determined.…”
Section: Telemedicinementioning
confidence: 99%
“…VR has been used to manage the pain and anxiety associated with medical procedures [ 16 ]. The literature identifies four types of VR: immersive virtual reality, non-immersive (desktop) virtual reality, augmented virtual reality and mixed virtual reality (a combination of real objects and environments with virtual people or places) [ 17 ]. The value of the application of immersive VR in clinical settings is that immersive VR environments can enable researchers or clinicians to modify multimodal input stimuli to make patients feel “present” in the projected environment [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the results of the present experiment, despite the small size of the study group, are an important addition to existing knowledge. Moreover, the review on the use of virtual reality in psychiatric disorders and rehabilitation [ 8 , 9 , 10 , 11 ] carried out by our team has demonstrated that there is a gap of scientific reports related to the possibility of using VR therapy, especially based on total immersion, in older patients with depression.…”
Section: Introductionmentioning
confidence: 99%